Nuclear imaging in the identification of aberrant vascular anatomy prior to hepatic arterial infusion - Tristan R. Lawson, MD; Jennifer A. Schroeder, MD (Radiology Case Reports, 2022)
Hepatic arterial infusion (HAI) pumps are a specialized therapeutic modality designed to deliver high dose local chemotherapy to hepatic metastases in carefully selected patients resulting in improved survival, with patients living an average of 2 years longer than those who did not receive HAI pumps. While beneficial, these chemoinfusion pumps require a multidisciplinary approach to ensure safe and effective treatment for the patient. Here, we present a case where scintigraphic evaluation by the nuclear medicine department directly affected management of a patient with a hepatic arterial infusion pump. Variant vascular anatomy was initially discovered on the postoperative Tc-99m MAA SPECT/CT and was ultimately embolized by interventional radiology prior to initiation of chemoinfusion. This case report demonstrates the utility of obtaining nuclear medicine scintigraphy prior to chemoinfusion in patients with hepatic arterial infusion pumps.